2010
DOI: 10.1177/2156759x1001400103
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Academic Engagement Among Immigrant Adolescents Through School-Family-Community Collaboration

Abstract: Schools are receiving students of immigrant origin in unprecedented numbers. Using an ecological framework, the authors reviewed the community, school, familial, and individual challenges that immigrant adolescent students encounter. They examined cognitive, relational, and behavioral dimensions of student engagement as well as culturally sensitive strategies for parental involvement. Varying academic trajectories were identified revealing that although some students performed at high or improving levels over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…Prior research identified three dimensions of engagement that are relevant for this study: cognitive, relational, and behavioral [32,46]. Cognitive engagement refers to the degree in which individuals are engrossed and intellectually involved in what they are learning.…”
Section: Engagement and Informednessmentioning
confidence: 99%
“…Prior research identified three dimensions of engagement that are relevant for this study: cognitive, relational, and behavioral [32,46]. Cognitive engagement refers to the degree in which individuals are engrossed and intellectually involved in what they are learning.…”
Section: Engagement and Informednessmentioning
confidence: 99%
“…In addition, their lack of a secure cultural identity is posited to contribute to gang membership and other unhealthy pursuits as a means of "belonging," or to feel protected during the adolescent years. Although, schools (Goh et al, 2007;Suarez-Orozco et al, 2010) and faith-based and cultural organizations can function as a healthy alternative to satisfy these needs, the most potent prophylactic is an intact family, particularly a strong extended family system (APA, 1998;Suarez-Orozco et al, 2002). This psychological fact has also been acknowledged by our judiciary.…”
Section: The Psychological Effects Of Immigrationmentioning
confidence: 91%
“…Yet even this opportunity may be compromised by poverty and, for migrant farm workers, the need for children's work and wages (APA, 1998). It may also be compromised by a plethora of challenges associated with poverty and discrimination including earlier lack of access to education, degree of cultural adaptation, and competency in written and spoken English (Goh, Wahl, McDonald, Brissett, & Yoon, 2007;Hagelskamp et al, 2010;Suarez-Orozco, Onaga, & de Lardemelle, 2010). Stressors, including direct and indirect experiences of and exposure to trauma as described earlier, also have the potential to profoundly affect children's well-being and development (Howe et al, 2008;Palmer et al, 1999).…”
Section: The Psychological Effects Of Immigrationmentioning
confidence: 92%
“…and exposure to school and community violence (Suárez-Orozco & Suárez-Orozco, 2001) have been cited as stressors that complicate their adjustment to school, leaving them vulnerable to academic failure. Suárez-Orozco et al (2010) noted that the risk of academic underachievement has enormous consequences on the postsecondary opportunities of immigrant youth in today's knowledge-based economy "where opportunities are limited for the undereducated" (p. 16). In this service-oriented, knowledge-based economy, high school dropouts are relegated to low-income jobs with little promise of mobility (Portes & Rumbaut, 2001).…”
mentioning
confidence: 99%